Service Delivery strategies and Poverty Reduction in Kidagoni Village, Zanzibar. - Makame, Ahmadakishindo. (Kabale University, 2020)
The study assessedservice delivery strategies and poverty reduction in Kidagoni village in Zanzibar. It showed the relationship between service delivery strategy and poverty reduction in Kidagoni Village North ‘A Unguja of Zanzibar. The people of Kidagoni village suffering from poverty, the indicators of poverty are lack of safe water, low level of education, poor transport, and poor quality of housing and poor health services.The objectives of the study were to assess the nature of service delivery strategy for poverty reduction, to examine the impact of service delivery strategies on poverty reduction and to examine the challenges service delivery strategies in poverty reduction inKidagoni village. The study was a cross sectional survey which employed both quantitative and qualitative approaches in data collection and analysis. Quantitative data was collected using questionnaire and qualitative data was collected using interviews. The service delivery strategy for poverty reduction of Kidagoni village activities reported that, Lack of safe water, Low level of education, Poor transport, and Poor quality of housing and poor health services. The impact of service delivery strategies on poverty reduction in Kidagoni village reported that, unemployment, Population expansion, Cultural distortion, Land scarp and Environmental degradation. The people of Kidagoni village facing many challenges service delivery strategies in poverty reduction. The challenges which include: Poor health services, Unequal distribution of resources, Climatic conditions, unemployment and increasing domestic needs. Finally the government of Zanzibar should encourage the services delivery in rural areas in order to achieve the objectives and improvement life standard to the people of Kidagoni village.